Albuminuria-lowering effect of dapagliflozin alone and in combination with saxagliptin and effect of dapagliflozin and saxagliptin on glycaemic control in patients with type 2 diabetes and chronic kidney disease (DELIGHT): a randomised, double-blind, placebo-controlled trial. Issue 6 (June 2019) - Pollock, Carol; Stefánsson, Bergur; Reyner, Daniel; Rossing, Peter; Sjöström, C David; Wheeler, David C; Langkilde, Anna Maria; Heerspink, Hiddo J L
Summary: Background: In patients with type 2 diabetes, intensive glucose control can be renoprotective and albuminuria-lowering treatments can slow the deterioration of kidney function. We assessed the albuminuria-lowering effect of the sodium-glucose co-transporter-2 inhibitor dapagliflozin with and without the dipeptidyl peptidase-4 inhibitor saxagliptin, and the effect of dapagliflozin–saxagliptin on glycaemic control in patients with type 2 diabetes and moderate-to-severe chronic kidney disease. Methods: In this double-blind, placebo-controlled trial (DELIGHT), we enrolled patients at 116 research centres in Australia, Canada, Japan, South Korea, Mexico, South Africa, Spain, Taiwan, and the USA. We included patients with a known history of type 2 diabetes, increased albuminuria (urine albumin-to-creatinine ratio [UACR] 30–3500 mg/g), an estimated glomerular filtration rate of 25–75 mL/min per 1·73 m 2, and an HbA1c of 7·0–11·0% (53–97 mmol/mol), who had been receiving stable doses of angiotensin-converting enzyme inhibitor or angiotensin II receptor blocker therapy and glucose-lowering treatment for at least 12 weeks. After a 4-week, single-blind placebo run-in period, participants were randomly assigned (1:1:1; via an interactive voice–web response system) to receive dapagliflozin (10 mg) only, dapagliflozin (10 mg) and saxagliptin (2·5 mg), or placebo once-daily for 24 weeks. Primary endpoints were change from baseline in UACR (dapagliflozin and dapagliflozin–saxagliptin groups) and HbA1c (dapagliflozin–saxagliptin group) at week 24 in all randomly allocated patients with available data (full analysis set). This study is registered withClinicalTrials.gov, numberNCT02547935 and is completed. Findings: The study took place between July 14, 2015, and May 18, 2018. 1187 patients were screened, of whom 461 were randomly assigned: 145 to the dapagliflozin group, 155 to the dapagliflozin–saxagliptin group, and 148 to the placebo group (13 patients were excluded because of data integrity issues). Dapagliflozin and dapagliflozin–saxagliptin reduced UACR versus placebo throughout the study period. At week 24, the difference ( vs placebo; n=134 patients with available data) in mean UACR change from baseline was −21·0% (95% CI −34·1 to −5·2; p=0·011) for dapagliflozin (n=132) and −38·0% (−48·2 to −25·8; p<0·0001) for dapagliflozin–saxagliptin (n=139). HbA1c was reduced in the dapagliflozin–saxagliptin group (n=137) compared with the placebo group (n=118) at week 24 (−0·58% [−0·80 to −0·37; p<0·0001]). The numbers of patients with adverse events (79 [54%] in the dapagliflozin group, 104 [68%] in the dapagliflozin–saxagliptin group, and 81 [55%] in the placebo group) or serious adverse events (12 [8%], 12 [8%], and 16 [11%], respectively) were similar across groups. There were no new drug-related safety signals. Interpretation: Dapagliflozin with or without saxagliptin, given in addition to angiotensin-converting enzyme inhibitor or angiotensin II receptor blocker treatment, is a potentially attractive option to slow the progression of kidney disease in patients with type 2 diabetes and moderate-to-severe chronic kidney disease. Funding: AstraZeneca.